Identification of Escherichia coli ygaQ and rpmG as novel mitomycin C resistance factors implicated in DNA repair - Bolt, Edward L.; Jenkins, Tabitha; Russo, Valeria Moreira; Ahmed, Sharlene; Cavey, James; Cass, Simon (Portland Press:, 2015)
Using the ASKA (A Complete Set of E. coli K-12 ORF Archive) library for genome-wide screening of E. coli proteins we identified that expression of ygaQ and rpmG promotemitomycin C resistance (MMCR). YgaQ mediated MMCR was independent of homologous recombination involving RecA or RuvABC, but required UvrD. YgaQ is an uncharacterized protein homologous to a-amylases that we identified to have nuclease activity directed to single stranded DNA of 5’ flaps. Nuclease activity was inactivated by mutation of two amino acid motifs, which also abolished MMCR. RpmG is frequently annotated as a bacterial ribosomal protein, although forms an operon with MutM glycosylase and a putative deubiquitinating enzyme, YicR. RpmG associated MMCR was dependent on MutM. MMCR from RpmG resembles DNA repair phenotypes reported for ‘idiosyncratic ribosomal proteins’ in eukaryotes.